Teknik Persuasif dalam Buku Sukses Tanpa Gelar Karya Andrias Harefa - Kartika Sari, Nina (GERAM: Gerakan Aktif Menulis, 2018)
This re search entitled persuasive techniques in a sussessful book without the title of Andrias Harefa work. The problem of research, how persuasive techniques, rationalization, identification, suggestion, conformity, compensation, replacement and projection in a successful book without a degree of work Andrias Harefa? Aims to describe, analyze, and intepret persuasive techniques, rationalization, identification, suggestion, conformity, compensation, replacement and projection in a successful book without the title of work Andrias Harefa. This research uses the theory proposed by Gorys Keraf 2004, using descriptive method. Data and data sources in this study is the contents of a successful book without the title Andrias Harefa work in 2005. This research method descriptive method, research type that is literature, and research approach that is qualitative. Data collection techniques used by the author is to classify data, analyze data, interpret data, and draw conclusions. Result of research about persuasive technique in success book without title of work of Andrias Harefa found existence persuasive technique counted 47 data or equal to 100% of them, rationalization used Andrias Harefa equal to 3 data or egual to 7%, identification used Andrias Harefa 31 data or equivalent to 67%, the suggestion used Andrias Harefa of 3 data or equaivalent to 7 %, the conformity used Andrias Harefa as much as 3 data or equivalent to 7%, replacement used Andrias Harefaas many as 4 data or equivalent to 9%, the projection used Andrias Harefa as much as 1 data or equivalent to 2%. Thus it can be concluded that the persuasive technique used by Andrias Harefa in a successful book without a title is more dominant using the technique of persuasive identification because a successful book without the title of work Andrias Harefa tends to use spsesial and interesting things to influence the reader, followed by replacemet, rationalization, suggestion, conformity, compensation, and projection.